Pengaruh Media Fun Thinkers Book Terhadap Kemampuan Berpikir Kritis Siswa Pada Materi Keragaman Budaya Sosial Kelas V SD Swasta Pelita - Surya Kartini Indah Sari Siregar; Eka Yusnaldi (LPPM Institut Pendidikan Nusantara Global, 2026)
This study aims to determine the effect of Fun Thinkers Book media on fifth-grade students' critical thinking skills in Social Studies learning, particularly on the topic of social and cultural diversity. The study employed a quantitative approach with a quasi-experimental method using a control group design. The sample consisted of 40 students from classes VA and VB of SD Swasta Pelita, divided into an experimental class and a control class. Data were collected through a critical thinking test based on indicators of analyzing, evaluating, and drawing conclusions, supported by a Likert-scale response sheet. The instruments were tested for validity and reliability before use. Data analysis included descriptive statistics, normality test, homogeneity test, and independent sample t-test. The results showed that the average posttest score of the experimental class was 83.10, while the control class obtained 52.65. The independent sample t-test produced a significance value of 0.000 < 0.05, indicating a significant difference between the two groups. These findings show that Fun Thinkers Book has a positive and significant effect on improving students' critical thinking skills in Social Studies learning. Therefore, this media can be used as an alternative interactive learning medium to create a more engaging, active, and meaningful learning process in elementary schools.